Examining of the relationship between sexting, cyber bullying, cyber victimization and self-harm behaviour in adolescents with online gaming disorder - Kitapcioglu, Sureyyanur; Aricak, Osman Tolga; Dinc, Mehmet; Kaya, Ilyas; Dinç, Mehmet; Arıcak, Osman Tolga (Akademıaı Kıado Zrt)
Meeting Abstract
Keywords: gaming disorder; cyberbulling; cyber victimization; sexting; self harm